2006
DOI: 10.1111/j.1423-0410.2006.00814.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of permanent national register of blood component use utilizing electronic hospital information systems

Abstract: Background and ObjectivesWe wanted to establish a permanent national database system, which can be utilized to study transfusion recipients and blood use in Finland. Materials and MethodsA regularly updated register for permanent use was developed. To study the usability of the database, years 2002 and 2003 were further analysed. Database included all transfused patients in major blood-transfusing hospitals from four university and five central hospital districts managing altogether 63% of Finnish inpatient ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 6 publications
1
21
0
2
Order By: Relevance
“…The data are collected on all potentially transfused patients using computer programs designed for data collection (VOK data extraction system, MediWare Corporation Oy, Helsinki, Finland; and Oulu data extraction system, Oulu, Finland). The validation of data has been described previously 1 . Currently 10 hospital districts provide data to the registry.…”
Section: Methodsmentioning
confidence: 99%
“…The data are collected on all potentially transfused patients using computer programs designed for data collection (VOK data extraction system, MediWare Corporation Oy, Helsinki, Finland; and Oulu data extraction system, Oulu, Finland). The validation of data has been described previously 1 . Currently 10 hospital districts provide data to the registry.…”
Section: Methodsmentioning
confidence: 99%
“…The significant decrease seen during the relatively short 6‐year study period was evident both in the rate of transfusions per population and in the amount of RBC units per patient. The number of single‐unit transfusions was significantly higher than before (Palo et al, ) and increased, showing growing adherence to evidence‐based practice. Nevertheless, 34% of transfusions were still double‐unit, and 58% of multiple‐unit transfusions were given in even numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown variations in blood use among hospitals and clinicians (Palo et al, 2006;Abdelsattar et al, 2015), indicating inappropriate blood use. The objective of RBC transfusion is to maintain adequate oxygen delivery to tissues, and the decision to transfuse cannot be based solely on laboratory parameters (Nielsen et al, 2017).…”
mentioning
confidence: 99%
“…Validation outcomes reported by previous transfusion data warehouse studies are sparse and vary greatly. Most often reported was the linkage rate of transfusions to donors, varying between 92%–99% [20, 2225] and, vice versa, estimates of wastage of blood products (i.e., issued but not transfused) of 1.3% and 7.7% [22, 23]. The percentage missing values was also reported by some studies: clinical variables were missing for 13% (post-transfusion Hb), 14% (ASA code) [26], and 20% (specialty), with the degree of missingness varying between specialties from 2% to 47% [21] (a more extensive overview per transfusion database is provided in Additional file 1: Table S3).…”
Section: Discussionmentioning
confidence: 99%